2021
DOI: 10.1021/acs.cgd.0c01230
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and Surface Effects on the Seed Orientation of Laser-Induced Sb2S3 Crystals on Sb-S-I Glass

Abstract: This study explores multiple fields as a mechanism of controlling the orientation of the nucleation process, which is generally believed to be a stochastic process, as observed in the equiaxed grain structure of glass ceramics. Specifically, as a model system, Sb2S3 single crystals are grown on the surface of Sb-S-I chalcogenide glass via laser crystallization. A spatial light modulator is used to configure the beam shape, thermal gradient, and/or polarization of the laser for controlling the orientation of Sb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…81 Light polarization has also been reported to affect the orientation of crystals formed in chalcogenide amorphous films. [110][111][112] Au-Yeung et al 113 reported similar results for laser-induced crystal growth of Sb 2 S 3 by cw laser on bulk Sb-S-I glass surface. The authors noted how changing the direction of polarization affected the direction of the most polarizable crystal axis.…”
Section: Light Polarizationmentioning
confidence: 57%
See 3 more Smart Citations
“…81 Light polarization has also been reported to affect the orientation of crystals formed in chalcogenide amorphous films. [110][111][112] Au-Yeung et al 113 reported similar results for laser-induced crystal growth of Sb 2 S 3 by cw laser on bulk Sb-S-I glass surface. The authors noted how changing the direction of polarization affected the direction of the most polarizable crystal axis.…”
Section: Light Polarizationmentioning
confidence: 57%
“…Light polarization has also been reported to affect the orientation of crystals formed in chalcogenide amorphous films 110–112 . Au‐Yeung et al 113 . reported similar results for laser‐induced crystal growth of Sb 2 S 3 by cw laser on bulk Sb‐S‐I glass surface.…”
Section: Control Of Crystal Orientationmentioning
confidence: 74%
See 2 more Smart Citations
“…Following this trend, we can argue that including Sulfur into PCM composition along with Se and Te could add new functionalities not explored so far in this class of materials. Such supposition is based on a recent renaissance of antimony and germanium containing sulfides and selenides, which are proposed as perspective medium for switchable, high-saturation, high-efficiency and high-resolution dynamic meta-pixels for enhanced meta-displays (Sb 2 S 3 and Sb 2 Se 3 ) 25 , monocrystalline path formation under laser irradiation (SbSI) 26 , 27 , 3D waveguides (Ge 23 Sb 7 S 70 ) 28 , solid-state lithium batteries (Ga 2 S 3 modified Ge 33 S 67 ) 29 and glass-on-graphene photonics 30 . Recently, Sb 2 S 3 and Sb 2 Se 3 compounds were proven to possess a phase-change memory effect too 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%